Entrepreneurs' Social Capital and the Economic Performance of Small Businesses: The Moderating Role of Competitive Intensity and Entrepreneurs' Experience - Hernández‐Carrión, Carlos; Camarero‐Izquierdo, Carmen; Gutiérrez‐Cillán, Jesús (Strategic Entrepreneurship Journal, 2017)
Research summary This article analyzes the personal, professional, associative, and institutional relationship networks in which the entrepreneur is involved and the resources embedded therein, and it proposes that an entrepreneur's social capital resources are determinants of his/her business' economic performance. The effect of social capital resources is moderated by competitive intensity in the industry and the entrepreneur's experience. A questionnaire survey and a sample of 951 small‐ and medium‐sized firms were used to test the proposed hypotheses. Results show that economic performance is influenced more by professional and institutional network resources than by the other network resources. However, competitive intensity reduces the effect of institutional resources and increases the relevance of personal resources, whereas the entrepreneur's experience in the sector reinforces the impact of professional and institutional resources. Managerial summary Insofar as small business entrepreneurs lack sufficient resources of their own to ensure the growth of their businesses, entrepreneurs' relationship networks can provide them with access to strategic resources. Hence, small business entrepreneurs must place all their own networks at the service of their firms. However, networks are not all equally advantageous, and each network does not prove equally advantageous in all situations. Our results show that professional and institutional networks generally contribute more to improving performance than do associative and personal networks. Moreover, as an entrepreneur's experience in the sector increases, so does the ability to exploit the advantages afforded by professional and institutional networks. In contrast, as industrial competitive intensity increases, so does the relevance of personal networks at the expense of institutional networks. Copyright © 2016 Strategic Management Society